Dysregulation of Wnt/β‐catenin signaling by protein kinases in hepatocellular carcinoma and its therapeutic application. Issue 5 (6th April 2021) - Li, Qian; Sun, Mengqing; Wang, Menglan; Feng, Mengqing; Yang, Fan; Li, Lina; Zhao, Jianbo; Chang, Cunjie; Dong, Heng; Xie, Tian; Chen, Jianxiang
Abstract: Wnt/β‐catenin signaling is indispensable for many biological processes, including embryonic development, cell cycle, inflammation, and carcinogenesis. Aberrant activation of the Wnt/β‐catenin signaling can promote tumorigenicity and enhance metastatic potential in hepatocellular carcinoma (HCC). Targeting this pathway is a new opportunity for precise medicine for HCC. However, inhibiting Wnt/β‐catenin signaling alone is unlikely to significantly improve HCC patient outcome due to the lack of specific inhibitors and the complexity of this pathway. Combination with other therapies will be an important next step in improving the efficacy of Wnt/β‐catenin signaling inhibitors. Protein kinases play a key and evolutionarily conserved role in the Wnt/β‐catenin signaling and have become one of the most important drug targets in cancer. Targeting Wnt/β‐catenin signaling and its regulatory kinase together will be a promising HCC management strategy. In this review, we summarize the kinases that modulate the Wnt/β‐catenin signaling in HCC and briefly discuss their molecular mechanisms. Furthermore, we list some small molecules that target the kinases and may inhibit Wnt/β‐catenin signaling, to offer new perspectives for preclinical and clinical HCC studies. Abstract : In this review, we summarize the kinases that modulate the Wnt/β‐catenin signaling in HCC and briefly discuss their molecular mechanisms. Furthermore, we list some small molecules that target the kinases and may inhibit Wnt/β‐catenin signaling to offer new perspectives for preclinical and clinical HCC studies.